Analisis Keterlambatan Audit Berdasarkan Rasio Laporan Keuangan Perusahaan Indonesia - Sulistyorini, Ariyana; Bayu Utomo, Rochmad (Income Journal: Accounting, Management and Economic Research, 2023)
Companies that experience delays in submitting audited financial reports in Indonesia have increased, until 9 May 2022 there were 91 issuers who received written warning I for not submitting financial reports. Finding out how profitability, solvency, and liquidity affected audit delays was the aim of this study. The theory used in this study uses agency theory. The selection of the samples was deliberate, involving 36 companies from various sectors such as consumer cyclicals, property & real estate, energy, consumer non-cyclicals, and industrial sectors listed on Indonesia's Stock Exchange between 2020 and 2021. The study utilized several data analytic techniques, namely multiple linear regression analysis, the F test, and the t test. Audit delay was used as the dependent variable while the independent variables consist of profitability, solvency and liquidity. Solvency positively impacted audit delay, and profitability, liquidity, and solvency simultaneously impacted it. Companies must pay attention to the timeliness of submitting audited financial reports to avoid asymmetric information and reduce the relevance of information in financial reports.